Acetyl α-d-2,3,4-triacetyllyxopyranoside - Shawn Culver; Jonathan S. Rhoad (IUCrData)
The structure of the title compound, C13H18O9, has monoclinic (P21) symmetry. It is of interest with respect to stereochemistry and the anomeric effect. Two acetyl subsituents adopt equatorial orientations and two are axial. The extended structure displays C—H...O hydrogen bonding.